2013
DOI: 10.1371/journal.pone.0076386
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of Potential Predictive Markers and Survival Data for a Response to Sunitinib in Patients with Metastatic Renal Cell Carcinoma

Abstract: BackgroundPatients with metastatic clear cell renal cell carcinoma (ccRCC) are frequently treated with tyrosine kinase inhibitors (TKI) such as sunitinib. It inhibits angiogenic pathways by mainly targeting the receptors of VEGF and PDGF. In ccRCC, angiogenesis is characterized by the inactivation of the von Hippel-Lindau gene (VHL) which in turn leads to the induction of HIF1α target genes such as CA9 and VEGF. Furthermore, the angiogenic phenotype of ccRCC is also reflected by endothelial markers (CD31, CD34… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 59 publications
4
42
0
Order By: Relevance
“…Dornbusch et al [56] evaluated the immunoexpression of tumor protein markers in 42 patients with mRCC. They concluded that HIF-1a, CA9, Ki67, CD31, pVEGFR1, VEGFR1 and -2, pPDGFR-a and -b were associated with the response to sunitinib (P < 0.05) [56].…”
Section: Protein Expression and Immunoexpression In Sunitinib Treatmentmentioning
confidence: 99%
“…Dornbusch et al [56] evaluated the immunoexpression of tumor protein markers in 42 patients with mRCC. They concluded that HIF-1a, CA9, Ki67, CD31, pVEGFR1, VEGFR1 and -2, pPDGFR-a and -b were associated with the response to sunitinib (P < 0.05) [56].…”
Section: Protein Expression and Immunoexpression In Sunitinib Treatmentmentioning
confidence: 99%
“…In addition, there is no clear-cut evidence that the ccRCC or the non-ccRCC histotypes respond differently to specific target therapies [9, 11]…”
Section: Introductionmentioning
confidence: 99%
“…RCC is resistant to chemo-and radiotherapy; thus, surgical resection is still the first choice treatment of RCC [4]. As RCC is difficult to recognize clinically, nearly 30 % of the patients present with distant metastases at the time of the diagnosis [5,6]. Up to now, the prognosis for advanced or metastatic RCC is poor [7].…”
Section: Introductionmentioning
confidence: 99%